AcehSeis project provides insights into the detailed seismicity distribution and relation to fault structures in Central Aceh, Northern Sumatra. (March 2019) - Muksin, Umar; Bauer, Klaus; Muzli, Muzli; Ryberg, Trond; Nurdin, Irwandi; Masturiyono, Masturiyono; Weber, Michael
Graphical abstract: Highlights: We studied the seismicity and detailed fault structure of Northern Sumatra. The seismicity distribution and the mechanisms correlate with the Sumatra Fault line. The seismicity reveals the activity of the secondary faults e.g. the Batee Fault. We found a new active fault, namely the Nisam Fault. Abstract: For the first time a dense seismic network (AcehSeis) consisting of 30 short-period seismic stations was installed for 10 months from July 2014 in order to record crustal earthquakes in Central Aceh, Northern Sumatra, following the hazardous earthquake with magnitude Mw. 6.1, July 2nd, 2013. The objective of this research is to investigate the active fault characteristics derived from local earthquake data combined with a digital elevation model. The network recorded more than 1790 local events occurring along the main Great Sumatran Fault (GSF) and its secondary faults. Local earthquakes with azimuthal gap angles greater than 180° were excluded to avoid non-unique earthquake locations. Therefore from all recorded earthquakes, 1127 local earthquakes were used for further seismological analysis. A method of simultaneous earthquake relocation and 1D velocity determination was applied to obtain better location of earthquakes. The output of the first relocated seismicity was then relocated again by using a double difference relocation method. After relocation, earthquakes are concentrated in a narrow zone along the active fault, indicating the reliability of the earthquake location. We then determined the focal mechanism of earthquakes, based on the first polarity picks. The seismicity distribution correlates with the well-known GSF and its main secondary faults. Earthquake locations also clearly revealed several active segments which include the Batee, Beutong, Tangse-Geumpang, Lampahan, Aceh and Seulimeum, and Nisam faults. Also less-known faults as the Pamue and Atu Lintang-Peusangan faults are imaged. In Northern Aceh an unknown earthquake cluster associated with an active fault, the Nisam Fault was detected, which is also visible in the topography. The seismicity along GSF is offset at around 96.7 E, constrained by the nearly N-S striking Atu Lintang-Peusangan Fault confirming the segmentation of GSF at this longitude. The Aceh segment and the Seulimum Fault in the northernmost region of the network are both active and clearly imaged by the seismicity. The Pamue and the Lampahan Faults seem to be the splay of GSF as indicated by identical strike direction as the GSF. The Lampahan fault is characterized by NW-SE seismicity lineation, which is in agreement with the focal mechanisms. The Laut Tawar Lake could be a part of the Lampahan Fault that is also offset at ∼96.7 E at the line of the Atu Lintang-Peusangan fault. The Burni Geureudong Fault on the other hand strikes ENE-WSW which suggests a conjugate fault of the Lampahan Fault.